2013
DOI: 10.1074/jbc.m113.494369
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Exerts a Protective Role in Ovalbumin-induced Neutrophilic Airway Inflammation by Inhibiting Th17 Cell-mediated Immune Response

Abstract: Background: Heme oxygenase-1 (HO-1) is an inducible enzyme that exerts multiple physiological functions. Results: Induction of HO-1 inhibits Th17-mediated neutrophilic airway inflammation in vivo and suppresses Th17 cell differentiation in vitro. Conclusion: HO-1 exhibits anti-inflammatory activity in non-eosinophilic asthma (NEA) by inhibiting Th17 responses. Significance: HO-1 may become a novel therapeutic target in NEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 60 publications
8
42
0
Order By: Relevance
“…The increased frequencies and enhanced suppressive activity of GARP + CD4 + CD25 + Tregs could effectively inhibit the hyperproliferation of Th1 cells to maintain immune homeostasis by direct cell-cell contact and the expression of anti-inflammatory cytokine TGF-β1. HO-1 has been shown to suppress Th17 cell-mediated immune response in some animal models [40,41]. Now, we further confirmed that HO-1 inhibited the Th17-dominant response in patients with ACS.…”
Section: Discussionsupporting
confidence: 80%
“…The increased frequencies and enhanced suppressive activity of GARP + CD4 + CD25 + Tregs could effectively inhibit the hyperproliferation of Th1 cells to maintain immune homeostasis by direct cell-cell contact and the expression of anti-inflammatory cytokine TGF-β1. HO-1 has been shown to suppress Th17 cell-mediated immune response in some animal models [40,41]. Now, we further confirmed that HO-1 inhibited the Th17-dominant response in patients with ACS.…”
Section: Discussionsupporting
confidence: 80%
“…Because HO-1 has pleiotropic immunomodulatory effects, there are already numerous illustrations of therapeutic applications of HO-1 in multiple experimental models of IBD mediated by various immune mechanisms (36 -38). Additionally, our previous studies have suggested that induction of HO-1 attenuates the airway inflammation in a mouse asthma model through promoting Tregs in eosinophilic airway inflammation (39,40) and inhibiting Th17 responses in non-eosinophilic airway inflammation (41). However, little is known about how HO-1 exerts immune regulatory effects under different inflammatory conditions.…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…The regulation of HO-1 expression in macrophages was strictly required for protection against mycobacterial infection in mice, and HO-1-deficient mice were more susceptible to intravenous mycobacterium avium infections, and failed to mount a protective granulomatous response in mice lacking mature B cells (91). In a mouse model of noneosinophilic asthma, HO-1 provided anti-inflammatory effects by inhibiting the p-STAT3-RORct pathway (120). HO can also work along with the scaffold protein caveolin-1 and negatively regulate TLR-4 signaling.…”
Section: Ho-1 Reduces Inflammationmentioning
confidence: 99%